Macroecology - Cooper, Natalie (Henry Stewart Talks, 2017)
What is macroecology?, Definitions, emergence as a field, Macroecological patterns, Species-area relationships, Body size-diversity, Body size-abundance, Abundance-range size, Bergmann's rule, Hotspots of species richness, Latitudinal diversity gradient, Biases, Modern macroecology, Mechanistic and predictive models